Metabolomics in food safety and quality control - Khatib, Alfi (2013)
Safety and quality control of food are hot issues in the production of food and its distribution, and are of primary concern to food and agriculture organization. Robust, efficient, sensitive, comprehensive and cost-effective analytical methodologies need to be developed to guarantee food safety and quality. Metabolomics approach is a potential analytical tool that fulfills this requirement. It is a new analytical approach following other developed ‘omics’ technologies, e.g. genomics and proteomics. Metabolomics is a comprehensive analytical method and considered as a high-throughput technique to identify and quantify of the metabolites in food. The subsequent statistical multivariate data analysis enables a general identification of expected metabolites in food. Metabolomics studies often include a high number of samples and there is thus a requirement of high-throughput analytical methods. In general, there are some analytical techniques that dominate the metabolomics methodologies; high-resolution proton nuclear magnetic resonance spectroscopy, liquid chromatography mass spectrometry, gas chromatography mass spectrometry, Fourier transform infrared spectroscopy, and capillary electrophoresis. Each of the different methodologies has its advantages and disadvantages, and often the techniques complement each other. We discuss in this presentation some examples on the use of metabolomics in food quality and safety control, and advantages of this technique beyond targeted analytical method. Several applications of metabolomics on detection of adulteration and chemical safety of food are reviewed. Adulteration of milk is one of hot topic in food safety especially after melamine issue in some years ago. Metabolomics is a potential tool to be used to avoid the same incidence in the future. Another example of the application is lard contamination in food. NMR and FTIR-based metabolomics in lard detection have been intensively developed for ‘halal’ certification. Finally, this approach have been used to detect genetically modified foods due to food safety issue.